Perlindungan Hukum Bagi Pencipta Film Terhadap Peredaran Digital Video Disk (DVD) Film Bajakan - Ali Mufthi, Fikri; Supianto, Supianto (WELFARE STATE Jurnal Hukum, 2022)
Currently, there are many entrepreneurs selling DVD films, which they sell or distribute in the form of digital video discs (DVD) for commercial purposes without asking permission from the creator or copyright holder for the work. Although the latest law has been enacted Law No. 28 of 2014 concerning Copyright. The method used in this paper is a normative law research method. explains the procedure for recording creations. The period of Copyright protection is regulated in Article 58 which states that Copyright Protection is valid for the life of the Creator and continues for 70 years after death starting from January 1 of the following year. Legal liability for Copyright violators based on Law Number 28 of 2014 concerning Copyright, namely through law enforcement in criminal, civil, and administrative ways.